2020
DOI: 10.1038/s41598-020-67052-z
|View full text |Cite
|
Sign up to set email alerts
|

Label-free, automated classification of microsatellite status in colorectal cancer by infrared imaging

Abstract: Challenging histopathological diagnostics in cancer include microsatellite instability-high (MSI-H) colorectal cancer (CRC), which occurs in 15% of early-stage CRC and is caused by a deficiency in the mismatch repair system. The diagnosis of MSI-H cannot be reliably achieved by visual inspection of a hematoxylin and eosin stained thin section alone, but additionally requires subsequent molecular analysis. Time-and sample-intensive immunohistochemistry with subsequent fragment length analysis is used. The aim o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 55 publications
0
16
0
Order By: Relevance
“…The upper right cell turns circa 90° between 35 and 52 min, but in between its image appears fuzzy, with stripes along the direction of the scan that repeats every 3 s, indicating this cell changes position irregularly on a time scale of several s. Lastly, a third cell seen in the middle of the image at 35 min, detected for a few consecutive scans only, begins to look fuzzy in the 30 min image after it had been in a well-defined shape for the preceding half hour. In the future such dynamics could be tracked with orders-of-magnitude higher frame rate, by using optical-parametric or quantum-cascade laser sources 5 , 28 , 29 .
Figure 5 Adhesion-localised, but mobile living E. coli cells, sequential s-SNOM infrared amplitude s 2 images as cells adhere, grow and move in the medium under a 15 nm SiN membrane (Norcada NBPX5002YZ-HR), at times (min) indicated, color scale as in Fig.
…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The upper right cell turns circa 90° between 35 and 52 min, but in between its image appears fuzzy, with stripes along the direction of the scan that repeats every 3 s, indicating this cell changes position irregularly on a time scale of several s. Lastly, a third cell seen in the middle of the image at 35 min, detected for a few consecutive scans only, begins to look fuzzy in the 30 min image after it had been in a well-defined shape for the preceding half hour. In the future such dynamics could be tracked with orders-of-magnitude higher frame rate, by using optical-parametric or quantum-cascade laser sources 5 , 28 , 29 .
Figure 5 Adhesion-localised, but mobile living E. coli cells, sequential s-SNOM infrared amplitude s 2 images as cells adhere, grow and move in the medium under a 15 nm SiN membrane (Norcada NBPX5002YZ-HR), at times (min) indicated, color scale as in Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…Pertaining spectra in the "fingerprint region" of wavelengths between 5 and 15 µm routinely determined by FTIR (Fourier-transform infrared) spectroscopy serve for quantitative chemical recognition in many fields of chemical analytics. This potential is also gaining increasing interest in the life sciences where, for example, advanced workflow procedures can classify embedded tumour tissue sections on the basis of minute spectral differences 5 .…”
Section: Introductionmentioning
confidence: 99%
“…The workflow with the RF classifier used for this work was established and described in previous publications. 29,35,36 The RF classifier was shown to be robust and reliable for tissue classification using IR imaging. 25,38e40 In this study, five consecutive RF classifiers were generated.…”
Section: Classifier Setup and Spectral Database Generationmentioning
confidence: 99%
“…In addition to the histochemical and immunohistochemical staining for subtyping lung cancer, the Institute of Pathology, University Hospital Cologne, sequenced an NGS gene panel to identify relevant mutations in lung tumor tissues. Previous studies showed that IR imaging can be used for biomarker identification, 26,28,36,44 otherwise performed by several IHC stainings. Therefore, to add a molecular dimension to the spatial IR resolution, herein, two additional RF classifiers were trained to identify mutations in lung cancer tissues (Figure 3).…”
Section: Analysis Of Mutations In Lung Adenocarcinomamentioning
confidence: 99%
See 1 more Smart Citation